HUBUNGAN RELATION BOREDOM PRONENESS DAN KECENDERUNGAN BERSELINGKUH PADA DEWASA AWAL YANG MENJALANI LDR - Sartica, Tasya; Sahrani, Riana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between relation boredom proneness and infidelity tendency among emerging adults who are in long-distance relationships (LDR). Long-distance relationships often limit direct interaction and shared experiences, which may increase feelings of boredom and potentially encourage infidelity tendencies. This study employed a quantitative correlational design using purposive sampling. Participants consisted of 405 emerging adults aged 21–40 years who were currently involved in long-distance romantic relationships. Data were collected using the Relation Boredom Proneness Scale and the Infidelity Tendency Scale, both of which demonstrated adequate validity and reliability. Data analysis was conducted using Spearman’s correlation test. The results revealed a positive and significant relationship between relation boredom proneness and infidelity tendency (r = 0.459, p < 0.001). This finding indicates that higher levels of boredom within romantic relationships are associated with a greater tendency to engage in infidelity. Additional analyses showed significant differences based on age and relationship duration, while no significant differences were found based on gender or relationship status. Overall, the findings suggest that relation boredom proneness is an important psychological factor that contributes to infidelity tendencies among emerging adults in long-distance relationships. Keywords: Relation Boredom Proneness, Infidelity Tendency, Emerging Adults, Long Distance Relationship